2016
DOI: 10.21914/anziamj.v57i0.9764
|View full text |Cite
|
Sign up to set email alerts
|

The effect of surface tension on free-surface flow induced by a point sink

Abstract: The steady, axisymmetric flow induced by a point sink (or source) submerged in an inviscid fluid of infinite depth is computed and the resulting deformation of the free surface is obtained. The effect of surface tension on the free surface is determined and is the new component of this work. The maximum Froude numbers at which steady solutions exist are computed. It is found that the determining factor in reaching the critical flow changes as more surface tension is included. If there is zero or a very small a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
(24 reference statements)
1
1
0
Order By: Relevance
“…The flow phenomena observed in this experiment is similar to the one observed by Lubin et al [2] and Hocking et al [8,9]. At a certain entrainment depth and at a certain flow rate a dip forms above the point sink on the surface of the lower fluid.…”
Section: A Inviscid Model Using Bernoulli's Principlesupporting
confidence: 88%
See 1 more Smart Citation
“…The flow phenomena observed in this experiment is similar to the one observed by Lubin et al [2] and Hocking et al [8,9]. At a certain entrainment depth and at a certain flow rate a dip forms above the point sink on the surface of the lower fluid.…”
Section: A Inviscid Model Using Bernoulli's Principlesupporting
confidence: 88%
“…The critical drawdown Froude number based on the depth of the withdrawn fluid layer for conditions in which interfacial waves wer not a significant factor is approximately 1. Later, Hocking et al [9] included the surface tension effect due to the curvature of the interface and concluded that the Froude number, based on the sink depth from the interface, represented the complete flow phenomenon and the surface tension adds a resistance to the withdrawal force.…”
Section: Introductionmentioning
confidence: 99%